Line segmentation of handwritten text using histograms and tensor voting - Babczyński, Tomasz; Ptak, Roman (Zielona Góra: Uniwersytet Zielonogórski)
There are a large number of historical documents in libraries and other archives throughout the world. Most of them are written by hand. In many cases they exist in only one specimen and are hard to reach. Digitization of such artifacts can make them available to the community. But even digitized, they remain unsearchable, and an important task is to draw the contents in the computer readable form.
Keywords: document image processing; handwritten text line segmentation; projection profile; text string; off-line cursive script recognition; ICDAR 2009 competition